Solusi Persamaan Schrodinger dengan Potensial Scraf II Hyperbolic menggunakan Pendekatan Semiklasik - Syukron, Ahmad Aftah; Elviyanti, Isnaini Lilis (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2022)
The particle system is affected by the Scraf II Hyperbolic potential. The solution for solving the Schrodinger equation with the Scraff II Hyperbolic potential uses a semiclassical approach, namely using the WKB approach. The WKB approach is used to obtain an equation for the energy spectrum that is affected by the Scraf II Hyperbolic potential. Keywords: The Schrodinger equation, Hyperbolic Scraf II potential, WKB approach